Plasmodium infection in a Leadbeater's possum (Gymnobelideus leadbeateri). Issue 8 (August 2016) - Scheelings, TF; McLaren, PJ; Tatarczuch, L; Slocombe, RF
Abstract : Case report: A wild‐caught, adult female Leadbeater's possum ( Gymnobelideus leadbeateri ) died while in captivity after suffering from chronic ill‐thrift that progressed to acute respiratory distress. On histopathological examination of tissues, the cause of death was determined to be severe acute pneumonia with pulmonary oedema associated with an intracellular protozoan parasite present within erythrocytes. Transmission electron microscopy was performed on lung tissues and organisms consistent for Plasmodium sp . were identified within numerous erythrocytes. Molecular characterisation of the parasite from DNA extracted from tissue blocks of fixed lung determined the organism to belong to the genus Plasmodium (100% similarity to Plasmodium species when a BLAST analysis was performed); however, speciation of the organism was not possible. Conclusion: This is the first report of Plasmodium sp. infection and subsequent disease in a native Australian mammal. The lifecycle of this parasite remains unknown. It is also unknown what effects haemoparasitism may have on the population dynamics of this endangered possum species.